Próba weryfikacji teorii kredytu kupieckiego w branży odzieżowej w Polsce - Sierpińska, Maria; Młodkowski, Paweł (An Attempt to Verify the Trade Credit in Cloth Industry in Pola, 2007)
The paper presents trade credit used and extended by cloth industry in Poland during period from 1998 to 2002. Review of trade credit theories serves as an interpretation basis for observed behavior. The paper is structured as follows. Section I is an introduction. Section II covers theories explaining incentives for extending and using trade credit. Features of the industry under analysis and theoretical incentives are compared. It serves in posing hypotheses about trade credit net position of cloth industry in Poland. Section III presents used measures of trade credit. Three financial analysis ratios serve as proxies for trade credit used and one for trade credit extended. Section IV presents empirical data used in this study. Section V presents scope of trade credit used. Section VI presents scope of trade credit extended. One indicator is used as a proxy for this category. Section VII concludes about observed trends and behavior and is followed by some closing remarks about expected future changes to economic conditions of the cloth industry and their influence on trade credit net position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 480-490